Acheulean breccias of Prince cave (Liguria, Italy): New insights and regional issues. (8th August 2016) - Rossoni-Notter, Elena; Notter, Olivier; Simone, Suzanne; Simon, Patrick
Abstract: Prince cave is located along the Liguro-provençal corridor, in Italy (Liguria). Between mountains and sea, in the heart of a refuge zone, this site is part of the Paleolithic complex of sites called Balzi Rossi or Grimaldi. The excavations led from 1966 to 2002 managed to unearth Acheulean industries in two distinct brecciated deposits. Former interdisciplinary studies and analysis attributed Br2 to MIS 7 (220, 000 ± 120/50 ka) and Br1 to MIS 6. With the aim to update the characterizations and the place of these assemblages within the regional Acheulean panorama, this work conducts for the first time an exhaustive study on the respective industries. It provides detailed data on their numerical distributions, territorial patterns, technical features, and technoeconomic strategies. The results leads undoubtedly to common behaviors but modulated by significant differences. Both groups were looking for available littoral pebbles as to shape heavy and large cutting tools, in particular in Br1 (n = 159) where they are better and wider represented (choppers, chopping-tools, handaxes, picks, unifacial, rostro-carinate, épannelé). Br2 (n = 290), richer in artefacts, delivers much fewer products among which larger choppers, chopping-tools and bifacial piece. In both cases, direct percussion with hard hammers is prevalent, but bipolar percussion and soft hammer (Br1) had also been employed in finalization phases. Furthermore, the corpuses always include large flakes coming from specific operating sequences of debitage. Local Ciotti flints and other semi-local hard siliceous materials (Perinaldo flints, microquartzite), collected on the ligurian littoral at 10–20 km to the east, were used for medium flakes productions and the confection of retouched tools. Western (15–20 km) and allochthonous (>30 km) procurements appear exclusive to Br2. However, Prince knappers shared the same techniques (direct percussion with hard hammers), methods (unifacial/bifacial Discoid, recurrent unipolar, bipolar, and centripetal Levallois, SSDA) and technoeconomic strategies (ramifications, recycling of isotropic materials, blanks, tools, in situ knapping and confections). Volumetric unipolar and orthogonal methods are only inventoried in Br2. Debitage schemes pursued the productions of unretouched elongated flakes and manufacturing of scrapers and denticulates. Br2 corpus revealed a better control and efficiency in this particular regard. Its operating sequences are longer, more complex and achieved. It offers also a more various toolkit (transversal scrapers, Clactonian and retouched notches, beaks, points, Tayac point, awls, end-scrapers). With a lower "pre-Mousterian" industry and a upper "final Acheulean", Prince industries complete and inform the Acheulean neighboring complex.